Personal archives: exploring ordinary individuals’ archiving practices and motivation - Cortez, Jasmine James E.
This study examined ordinary individuals' personal archives and archiving practices. Researchers in archival studies have expressed the need to explore this topic further, as it has often been overlooked despite its historical and evidential value. By conducting a study on ordinary individuals through qualitative interviews and by adopting Sue McKemmish's concept of “Evidence of Me,” this study presented how ordinary individuals embody the essence of personal archiving and how their archives reflect their identities and personal histories.